1983
DOI: 10.1007/bf00275942
|View full text |Cite
|
Sign up to set email alerts
|

Insulin immunogenicity in pregnancy: maternal and fetal studies

Abstract: Antibodies to insulin were found in 92% of the 138 insulin-treated pregnant diabetic patients studied. No effect of pregnancy was shown on insulin antibody levels. Higher insulin antibody levels were significantly associated with the previous use of conventional insulins. Change from conventional to highly purified porcine insulin during pregnancy produced a significant reduction in insulin antibody levels. The combination of protamine zinc and soluble insulin used before pregnancy was found to be the most imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Menon et al (63) reported that the concentration of animal insulin in cord serum correlated with birth weight, but this observation has not been confirmed by other authors (42,64,65,70,71). The underlying mechanism would be an IAfacilitated maternal insulin transfer and, as a consequence, an enhancement of fetal hyperinsulinism and related morbidity (72).…”
Section: Dras and Diabetic Pregnancymentioning
confidence: 94%
See 2 more Smart Citations
“…Menon et al (63) reported that the concentration of animal insulin in cord serum correlated with birth weight, but this observation has not been confirmed by other authors (42,64,65,70,71). The underlying mechanism would be an IAfacilitated maternal insulin transfer and, as a consequence, an enhancement of fetal hyperinsulinism and related morbidity (72).…”
Section: Dras and Diabetic Pregnancymentioning
confidence: 94%
“…They are mainly IgG and are actively transported by the placenta (67,68). Maternal and fetal levels are highly correlated for IAs (42,60,(63)(64)(65), ICAs (60), GADAs (60,69), and IA-2As (60). This transplacental passage of antibodies lies behind the higher prevalence of DRA in cord blood from infants of diabetic mothers compared with infants of diabetic fathers (66).…”
Section: Dras and Diabetic Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that IA levels in women with type 1 diabetes remain quite stable during pregnancy [11,12] or decrease only slightly toward term [13,14]. At the time of delivery, it has been shown that around 74% to 90% of mothers with type 1 diabetes are IA-positive [15,16].…”
Section: Type 1 Diabetes-associated Antibodies During Pregnancymentioning
confidence: 98%
“…Controversially, some studies have reported stable IA titres during pregnancy [7,8], while a slight decrease in IA levels has been documented in others [9,10]. No detailed data are available on IAA levels in nondiabetic women during pregnancy.…”
Section: Introductionmentioning
confidence: 99%